PENANAMAN PENDIDIKAN NILAI KARAKTER DALAM TARI SUNARYANAM WIDYA ANANDAM DI SMP SUNARI LOKA KUTA (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The purpose of this study was to determine the inculcation of the value of character education in learning dance in Sunaryanam Widya Anandam dance at SMP Sunari Loka Kuta. This type of research is qualitative research. Another primary data source is in the form of photos of the Sunaryanam Widya Anandam dance at SMP Sunari Loka, Kuta. Secondary data sources are data obtained from reading writings, books written by others, sources from libraries and information that is relevant and related to the issues discussed. The data source of this research is in the form of discography, which is the data in the form of photos of the types of motion that are attracted by students. Overall semiotic analysis found ten character education values ​​contained in the Sunaryanam Widya Anandam dance at SMP Sunari Loka Kuta including, religious values, polite values, discipline values, responsibility values, creative values, love values, hard work values, independent values. , spirit of nationality, social care. The results showed that the value of character education in the Sunaryanam Widya Anandam dance at SMP Sunari Loka Kuta had a positive impact on students both individually and in groups. Students seem to be more dexterous in teaching their group of friends who still do not understand, and appear to be more focused when given instructions on the surgery of the dance movements being taught.